Investigation and application development of dynamic ergonomics - Koh, Yuen Qing (Nanyang Technological University, 2023)
Ergonomics is a multidisciplinary field of study that combines knowledge across various subjects such as anthropometry, psychology, physiology etc. Various interventions have been put in place to reduce the incidence of work-related musculoskeletal disorders (WMSDs), however, office workers are still reporting discomfort in various parts of their body such as the neck, shoulders, upper back, lower back etc. Accordingly, extensive research was done in this project to study and identify lack in areas of intervention and explore new innovation for addressing these WMSDs. The scope of this project includes the investigation, application and development of the novel concept of dynamic ergonomics. Following the definition of the concept, an embryonic framework for incorporating dynamic ergonomics into product design has been developed. The framework was then tested through application to the design of a portable dynamic visual display stand. In future, the concept can be further developed through conferences involving more professionals and the framework can be further refined through feedback from designers who attempt to include this concept into their design.